2023
DOI: 10.25259/sni_1096_2022
|View full text |Cite
|
Sign up to set email alerts
|

Middle meningeal artery embolisation: The review of a new treatment for chronic subdural hematomas

Abstract: Background: This is a literature review aiming to provide an update about the recent findings related to the efficacy of middle meningeal artery embolization (MMAE) in the treatment of chronic subdural hematomas (cSDHs), comparison with conventional therapy and deduction of the current recommendations and indications. Methods: The literature is reviewed using a search through the PubMed index using keywords. Studies are then screened, skimmed, and thoroughly read. 32 studies fulfilled the inclusion criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 80 publications
(156 reference statements)
0
4
0
Order By: Relevance
“…Although several recent studies have explored the relative safety and efficacy of MMAE vs burr hole drainage, none of those studies has reached level I scientific rigor. Indeed, there are several ongoing multi-center, prospective, randomized studies being conducted to address the role of efficacy of MMAE [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although several recent studies have explored the relative safety and efficacy of MMAE vs burr hole drainage, none of those studies has reached level I scientific rigor. Indeed, there are several ongoing multi-center, prospective, randomized studies being conducted to address the role of efficacy of MMAE [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] It has been reported that increase in antithrombotic use, aging of the population, alcoholism, neurological and systemic diseases due to brain atrophy, hemodialysis, low intracranial pressure and dural rupture associated with an increased risk of SDH. [5,8] The clinical presentation of SDH is highly variable. Patients typically present with confusion, headache, and loss of consciousness.…”
Section: Introductionmentioning
confidence: 99%
“…SDH appears as a crescent-shaped mass with a hypodense to isodense consistency on cranial computed tomography. [5][6][7][8][9][10] Treatment for SDH can be conservative or surgical, depending on symptoms and clot size. Complications and relapses are reported to be common.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers involved in this prospective case series hypothesized about the results of MMAE and the findings associated with its application. This study aims to evaluate the use of MMAE, drawing on an algorithm devised from previous and recent systematic reviews of MMAE for the treatment of cSDHs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%